Missing witches : recovering true histories of feminist magic - Dickens, Risa, 1980-; Torok, Amy, 1977- (North Atlantic Books, 2021)
"A guide to invocations, rituals, and histories at the intersection of magic and feminism, as informed by history's witches--and the sociopolitical culture that gave rise to them"--